Current Status of Vancomycin Analytical Methods - Do Nascimento, Patricia Aleixa [UNESP]; Kogawa, Ana Carolina [UNESP]; Nunes Salgado, Herida Regina [UNESP] (Oxford Univ Press Inc, 2020)
Background: The glycopeptide antibiotics are a class of antimicrobial drugs that are an important alternative for cases of bacterial infections resistant to penicillins, besides being able to be used to treat infections in people allergic to pencilin. They have great activity against Gram-positive microorganisms, including methicillin-resistant Staphylococcus aureus (MRSA), by inhibiting the cell wall synthesis. Objective: There are many analytical methods in the literature for determination of antimicrobial glycopeptide vancomycin in different matrixes that are very effective; however, all of them use toxic solvents, contributing to the generation of waste, causing damage to the environment and to the operator, as well as increased costs of analysis. Results: The most prevailing method found was high performance liquid chromatography (HPLC), followed by microbiological assays and, in less quantity, spectrometric methods. The chromatographic methods use organic solvents that are toxic, such as acetonitrile and methanol, and buffer solutions, that can damage the equipment and the column. In the microbiological assays the disc diffusion methods are still in the majority. The spectrophotometric methods were based in the UV-Vis region using buffer solutions as a diluent. Conclusions: All these methods can become greener, following green analytical chemistry principles, which could bring benefits both to the environment and the operator, and reduce costs. Highlights: In this paper, a literature review regarding analytical methods for determination of vancomycin was carried out with a suggestion of greener alternatives.